2021
DOI: 10.1186/s12891-021-04641-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, beliefs, and needs of Japanese people with knee osteoarthritis during conservative care: a qualitative study

Abstract: Background Patients’ perceptions and beliefs of disease could be influenced by their lifestyle and culture. Although it is important to understand their perceptions and beliefs toward disease to prevent and manage osteoarthritis (OA) through conservative care, this topic has not been investigated in Japanese people with knee OA. Therefore, this qualitative study aims to clarify how Japanese patients with knee OA experience and perceive their symptoms and disabilities, and how they face them dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…On the other hand, a recent systematic review indicated that Asian people with arthritis experience a ‘lonely path’ that is not shared with others to avoid being considered as complainers [ 48 ]. Japanese people with knee OA may internalize their complaints so they do not bother others [ 49 ]. These cultural differences are possible explanations for the difference in PCS, especially in helplessness, identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent systematic review indicated that Asian people with arthritis experience a ‘lonely path’ that is not shared with others to avoid being considered as complainers [ 48 ]. Japanese people with knee OA may internalize their complaints so they do not bother others [ 49 ]. These cultural differences are possible explanations for the difference in PCS, especially in helplessness, identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence also focuses on evaluating preoperative psycho-social factors as they could influence functionality, disability and perceived pain in patients with RCT [ 2 ]. Besides pathoanatomical structures, neurophysiological rules also provide for the patient’s pain experiences [ 10 , 11 ]. In a study by Lau et al, patients with rotator cuff tears showed preoperative depression and/or anxiety [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Norway, the rate of the patients who adhered to non-pharmacological conservative treatment methods was 44% [18]. Although there are qualitative studies in the literature aimed at determining patients' knowledge levels [19], their perspectives [20,21] and needs [22] regarding conservative treatment, no studies have been conducted on this subject in Turkey. Patients' perception of the disease and difficulties they experience during the disease process may be affected by sociocultural differences [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are qualitative studies in the literature aimed at determining patients' knowledge levels [19], their perspectives [20,21] and needs [22] regarding conservative treatment, no studies have been conducted on this subject in Turkey. Patients' perception of the disease and difficulties they experience during the disease process may be affected by sociocultural differences [22]. Although understanding difficulties experienced by patients during the conservative treatment of knee osteoarthritis is of great importance, this issue has not been adequately investigated in Turkey.…”
Section: Introductionmentioning
confidence: 99%